Women's Police Stations and Intimate Partner Violence : Evidence from Brazil - Perova, Elizaveta (Elsevier, 2017)
Although women's police stations have gained popularity as a measure to address intimate partner violence (IPV), there is little quantitative evaluation of their impacts on the incidence of IPV. This paper estimates the effects of women's police stations in Brazil on female homicides, a measure of the most severe form of IPV. Given that a high fraction of female deaths among women ages 15–49 years can be attributed to aggression by an intimate partner, female homicides appear the best proxy for severe IPV considering the scarcity of data on IPV in Brazil. We assemble a panel of 2074 municipalities from 2004 to 2009 and apply a difference-in-differences approach using location and timing to estimate the effect of establishing a women's police station on the municipal female homicide rate. Although we do not find a strong association on average, women's police stations appear to be highly effective among young women living in metropolitan areas. Establishing a women's police station in a metropolitan municipality is associated with a reduction in the female homicide rate by 1.23 deaths per 100,000 women ages 15–49 years (approximately a 17 percent reduction in the female homicide rate in metropolitan municipalities). The reduction in the homicide rate of women ages 15 to 24 is even higher: 5.57 deaths per 100,000 women. Better economic opportunities and less traditional social norms in metropolitan areas may explain the heterogeneous impacts of women's police stations.